Crystal structure of 2-[(2-acetoxyethoxy) methyl]-3-amino-1,2,4-triazin-5(2H)-one - Lee, Gene-Hsiang; Hwang, Long-Chih (International Journal of Advanced Chemistry, 2017)
The X-ray structural investigations has been carried out for the title compound, 2-[(2-acetoxyethoxy)methyl]-3-amino-1,2,4-triazin-5(2H)-one (1-[(2-acetoxyethoxy)methyl]-6-azaisocytosine), molecular formula C8H12N4O4, crystallizes in a monoclinic space group P-1 with a = 5.3124(3) Ã…, b = 7.3635(3) Ã…, c = 14.0170(8) Ã…, Î± = 81.5265(19)Â°, Î² = 85.852(2)Â°, Î³ = 76.760(2)Â°, V = 527.49(5) Ã…3 and Z = 2, resulting in a density, Dcalc, of 1.437 g/cm3. The hydrogen-bonding systems assemble with N-HÂ·Â·Â·O [graph set C (6)], N-HÂ·Â·Â·N [graph set R Â (8)], and N-HÂ·Â·Â·N combine with N-HÂ·Â·Â·O [graph set R (12)]. The side chain of the molecular structure is further stabilized by short contacts formed by intermolecular C-HÂ·Â·Â·O interactions.